Neuroimage of Voluntary Movement: Topography of the Bereitschaftspotential, a 64-Channel DC Current Source Density Study - Cui, R.Q.; Huter, D.; Lang, W.; Deecke, L. (NeuroImage (Orlando, Fla.), 1999)
The Bereitschaftspotential (BP) was recorded at 56 scalp positions when 17 healthy subjects performed brisk extensions of the right index finger. Aim of the study was to contribute to our understanding of the physiology underlying the BP and, in particular, to specify the situation at BP onset. For this purpose, the spatial pattern of the BP was analyzed in short time intervals (35 and/or 70 ms) starting 2.51 s before movement onset. For each time segment a spherical model of the BP was calculated by using spline interpolation. Then the spatial distribution of the electric potential at the scalp surface was transformed into a spatial distribution of current source densities (CSD map). Onset times of the BP and onset times of initial CSD-activity ranged between 2.23 and 1.81 s before movement onset. We selected a time window between 1.6 and 1.5 s before movement onset in order to analyze the spatial CSD pattern in each subject. In 10 subjects there was a significant current sink in the scalp area located over medial-wall motor areas (pre-SMA, SMA proper and anterior cingulate cortex: electrode positions C1, C2, FCz, Cz) in the absence of a significant current sink over the primary motor cortex (MI: electrode positions C3, CP3, and CP5). In three subjects significant current sinks were present at both sites and in another three subjects a current sink only over the lateral motor cortex was observed. In one subject no significant current sinks were measured. It is concluded that there is a large group of subjects (13/17) in whom BP at onset is associated with a current sink over medial-wall motor areas. At a later time interval (0.6 to 0.5 s before movement onset), significant current sinks were found in 13 subjects in medial and in 10 subjects in lateral recordings. These data were considered to be consistent with the hypothesis that, at least in a majority of subjects, medial-wall motor areas are activated earlier than lateral motor areas when organizing the initiation of a simple self-paced movement. Surface-recordings of the EEG do not allow further specification of cortical areas, which contribute to the current sinks. But in context with the current literature of the electrophysiology of nonhuman primates and of brain imaging in humans it is suggested that SMA and anterior cingulate cortex contribute to the current sink, the fronto-central midline, and that the primary motor cortex (MI) contributes to the current sink in the scalp area, which is located above MI and closely posterior to it.